2020
DOI: 10.4103/jispcd.jispcd_416_19
|View full text |Cite
|
Sign up to set email alerts
|

Dentists’ willingness to report suspected violence cases in Saudi Arabia

Abstract: A BSTRACT Background and Aim: Violence is a life-threatening issue that mainly affects head and neck areas. Dentist might be the first person to notice this type of injury. This study aimed to investigate dentists’ willingness to report suspected violence exposure of their patients and factors associated with their willingness. Materials and Methods: In a cross-sectional study of 363 dentists in Riyadh, Saudi Arabia, a previously validated sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Similarly, updating the information and reporting more than five years of clinical experience were significant determinants for the practitioners to report wider case management skills. Moreover, a recent study on the willingness to report suspected violence cases by dentists also practicing in Saudi Arabia concluded that the lack history of previous training in abuse management is a predictor for the ability of dentists to detect signs of violence as well as their willingness to report suspected violence exposure 15 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, updating the information and reporting more than five years of clinical experience were significant determinants for the practitioners to report wider case management skills. Moreover, a recent study on the willingness to report suspected violence cases by dentists also practicing in Saudi Arabia concluded that the lack history of previous training in abuse management is a predictor for the ability of dentists to detect signs of violence as well as their willingness to report suspected violence exposure 15 …”
Section: Discussionmentioning
confidence: 99%
“…According to Polyzois et al, 28 the type of undergraduate academic training that the dentist has received does not affect their subsequent continuing education during professional practice but depends more on other factors such as family, demographic, or professional circumstances. However, they have shown to adopt a proactive behaviour against violence and to install a protective policy after receiving adequate undergraduate and postgraduate training 14,15,24,26,27 . The competences needed to practice dentistry in addition to academic training include operational mental attitudes to successfully face challenging situations 29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations